miRNA in multiple sclerosis: search for novel biomarkers - Gandhi, Roopali (Multiple sclerosis, 2015)
A major challenge in multiple sclerosis (MS) is to develop biomarkers that could help in understanding individual MS patients, i.e. whether they are a responder or non-responder to therapy, which medicine is more effective, and the degree to which they may be entering the progressive phase of disease. In the last few years, a lot of attention has been drawn toward identification of diagnostic, prognostic, process-specific, and treatment-related biomarkers for MS. In this review, we will focus on the micro RNAs (miRNAs) as potential candidates for MS biomarkers.